2013
DOI: 10.4236/ajps.2013.41014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonpolar Components from Ginseng of Different Ages

Abstract: Nonpolar components from ginseng of different ages were extracted and analysed using a GC-MS technique to determine their chemical compositions. In total, 23 ingredients, mostly aliphatic compounds, were identified. The compounds extracted included 10,12-octadecadiynoic acid (12.81% -36.43%), falcarinol (4.95% -36.79%), n-hexadecanoic acid (0.60% -9.70%), 9,12-octadecadienoic acid, ethyl ester (0.33% -5.63%), 5,7-dodecadiyn-1,12-diol (0.97% -3.85%), (Z)-9-octadecenamide (2.66% -5.38%) and (Z,Z)-9,12-octadecadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…At present, the chemical changes of herbal medicines are typically measured by tools such as liquid chromatography and gas chromatography . Chemical analysis is the method of choice to estimate the content of specific substances (either as medical or toxic substance) of herbal materials.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the chemical changes of herbal medicines are typically measured by tools such as liquid chromatography and gas chromatography . Chemical analysis is the method of choice to estimate the content of specific substances (either as medical or toxic substance) of herbal materials.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids with 12-24 atoms of carbon were identified, with C18:2 as the predominant component, followed by C16:0, C18:1, and C18:3. Zhang et al 24 also detected C16:0 and C18:2 from 70% ethanol extract of P. ginseng by GC-MS equipped with HP-5ms.…”
Section: Ginseng Lipid Components and Their Analysismentioning
confidence: 98%
“…45 Zhang et al 24 reported that the highest sitosterol content was observed in 6-year-old ginseng, but the levels dramatically decreased in older ginseng.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our experimental data showed that the cell viability of all GRE groups significantly higher than that of control group from the 32-hour point to the 48-hour point, meaning that GRE increased rather than inhibited the proliferation of K562 cells. One of the possible reasons is that except for ginsenosides and polysaccharides, there are some nonpolar chemical constituents in the GRE, such as polyacetylenes [8], flavonones and fatty acids, which might contribute to the effects of ginseng [1,2]. In this study, these other constituents account for a high percentage in the GRE (from 30.06% to 63.48%, Table 2) and possibly lead to the strong proliferation on K562 cells or change the combined effects via antagonism and/or synergy [9].…”
Section: Discussionmentioning
confidence: 99%